Analisis Perlakuan Akuntansi dalam Transaksi Mata Uang Asing terhadap Risiko Keuangan PT. Ramayana Lestari Sentosa Tbk - Hana Setiyaningsih; Dila Resti Kamila; Erinda Ayu Permatasari (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research aims to determine foreign currency transactions that occur at PT. Ramayana Lestari Sentosa Tbk in its financial reports is because countries have different currency values. Foreign currency transactions at this company involve the sale and purchase of currency to support business needs and control company risks. The data collection technique used in this research is a qualitative descriptive method. The results of the discussion stated that, PT. Ramayana Lestari Sentosa Tbk noted that foreign currency transactions occur due to import-export, foreign funding and foreign investment. Foreign currency transactions are important in company risk management as a source of good financial strategy.